Inflammatory cytokines synergize with the HIV-1 Tat protein to promote angiogenesis and Kaposi's sarcoma via induction of basic fibroblast growth factor and the alpha v beta 3 integrin. - Barillari, Giovanni; Sgadari, Cecilia; Palladino, Clelia; Gendelman, R; Caputo, Antonella; Morris, C B; Nair, B. C.; Markham, P; Nel, A; Stürzl, Michael; Ensoli, Barbara (Journal of Immunology, 1999)
The Tat protein of HIV-1, a transactivator of viral gene expression, is released by acutely infected T cells and, in this form, exerts angiogenic activities. These have linked the protein to the pathogenesis of Kaposi's sarcoma (KS), a vascular tumor frequent and aggressive in HIV-1-infected individuals (AIDS-KS). In this study, we show that a combination of the same inflammatory cytokines increased in KS lesions, namely IL-1 beta, TNF-alpha, and IFN-gamma, synergizes with Tat to promote in nude mice the development of angioproliferative KS-like lesions that are not observed with each factor alone. Inflammatory cytokines induce the tissue expression of both basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF), two angiogenic molecules highly produced in primary KS lesions. However, bFGF, but not VEGF, synergizes with Tat in vivo and induces endothelial cells to migrate, to adhere, and to grow in response to Tat in vitro. Tat angiogenic effects correlate with the expression of the alpha v beta 3 integrin that is induced by bFGF and binds the arginine-glycine-aspartic acid (RGD) region of Tat. In contrast, no correlation is observed with the expression of alpha v beta 5, which is promoted by VEGF and binds Tat basic region. Finally, KS lesion formation induced by bFGF and Tat in nude mice is blocked by antagonists of RGD-binding integrins. Because alpha v beta 3 is an RGD-binding integrin that is highly expressed in primary KS lesions, where it colocalizes with extracellular Tat on vessels and spindle cells, these results suggest that alpha v beta 3 competitors may represent a new strategy for the treatment of AIDS-KS.